Representasi Konsep Transformasi Geometri Melalui Pembelajaran Etnomatematika Menggunakan Sumber Objek Budaya Klenteng Sam Poo Kong - Indah Ayu Kusumawardani; Vivi Anggraini Saputri Azis; Iin Ariyas Setyawati; Adi Satrio Ardiansyah (ARITHMETIC: Academic Journal of Math, 2023)
The low mathematical understanding and reasoning skills of students along with abstract mathematical concepts make it difficult for students to understand mathematical concepts. So, new development innovations are needed in presenting mathematics learning to improve students' basic math skills. This research aims to explore the buildings in the Sam Poo Kong temple in finding mathematical concepts. This research is exploratory, the research method used is descriptive-qualitative, and the approach is ethnography because it studies cultural phenomena in society. The results of this study show that in the Sam Poo Kong temple there are ethnomathematics concepts related to geometric transformation material including 1) translation on the roof, pillars, and statues; 2) reflection on the overall structure of the temple building, ornaments, and the entrance gate of Sam Poo Kong; 3) rotation on lanterns and walls of hope; and 4) dilation on the structure of the roof and lanterns. From the research, it can be concluded that Sam Poo Kong temple presents the concept of geometry transformation, namely translation, reflection, rotation, and dilation.